Evaluación de agentes biocidas en el control e inhibición de microorganismos que generan desgaste en el recubrimiento de tanques de combustible (2020)
To diagnose the current state of the storage tanks, the surveys in different ESDs were analyzed in order to evaluate the control and fuel quality management practices and also inquire about the staff's knowledge about microbiological contamination and its consequences Also, samples were analyzed in order to evaluate the conditions in which the stored fuel is found together with the camera inspections that allowed to detect the unwanted effect of high microbiological concentrations in the material. To deepen the degradation of the reinforced polymer, mechanical, chemical and thermal tests were performed in order to assess its resistance against different conditions that a storage tank may experience and, on the other hand, the effect that biocidal agents have on the same The specific analyzes that the composite materials were most affected in the diesel media (B10) with high microbiological load and pure biocide, this is mainly due to the action of the microorganisms in the points of greater susceptibility of material and also, by the aggressiveness of alkaline solutions, affecting their thermal stability, stiffness, resistance and chemical structure.